ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERAN SERTA MASYARAKAT MEMELIHARA LINGKUNGAN PERKOTAAN DI KOTA MAKASSAR - Mulyadi Mulyadi (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The subject intended to study in this research was the role of community in preserving the city environment in Makassar city. Therefore the aim of this research was to know some factors influencing the role of community in preserving the city environment in Makassar city. The design of this research was a survey in quantitative approach. The scope of research covered three groups of different settlement in Makassar city namely (1) elite settlement group, (2) middle settlement group, and (3) crowded settlement group. The population of this research were the community who lived in Makassar city. Total sample were 300 household leader selected by using random sampling. The variable of this research were the role of community in preserving the environment as the dependent variable, knowledge about the ecosystem, knowledge as the life environmental, knowledge about the conservation, knowledge about the environmental pollution, know ledge about environmental preservation, behavior on the environmental concern, education level, income level, resource available in family and clean culture as the independent variable. To know the description of community role in preserving the environment, it was used the descriptive statistic analysis. To know some factors influencing the role of community it was used inferential statistic analysis. The models of analysis was multiple regression analysis. The results showed thet (1) the community participation in preserving the city environment in Makassar city viewed from conservation aspect, pollution handling and environmental conservation included in low category, (2) community knowledge about the city ecosystem, life environment, conservation, live environment pollution, city environment conservation included in low category, (3) the community behavior towards the city environment classified positive and the concern towards the environment classified care, (4) the knowledge about the ecosystem issue of city, life environment issue, environmental conservation issue, life environmental pollution issue, city environmental preservation issue, care towards the environment, education level, and clean culture influenced positively towards the community participation in preserving the city environment in Makassar city, and (5) the income level, and available resources in a household didn’t influenced towards the community participation in preserving the city environment in Makassar city.